“Answering the challenges of healthcare services: A study of the effectivness of mobile JKN as a BPJS digital innovation in Sibolga 2025” - Situmorang, Benri; Gunawan, Roni; Herlina, Herlina (Journal of Midwifery and Nursing, 2025)
The National Health Insurance (JKN) mobile application provides convenience for BPJS participants. This convenience includes paying BPJS contributions, updating participant data, accessing family member data, and more. The purpose of this study was to specifically evaluate the perceived effectiveness and practical benefits of the JKN mobile application in improving service access among users in Sibolga City. This research employed a descriptive qualitative method, involving four purposively selected informants: two BPJS Health officers and two active users of the JKN application. Data were collected through in-depth interviews, direct observation, and document review. The study found that the JKN mobile application significantly enhances healthcare service accessibility and user autonomy. Informants reported that essential features-such as digital membership cards (E-ID), online queue registration (antrean online), and contribution tracking-were particularly useful in reducing administrative burden and time. Users no longer need to physically visit the BPJS Health office, as the application-readily available on the Play Store-enables them to access services anytime and anywhere.